Pharmacokinetics of Oral Prednisone at Various Doses in Dogs: Preliminary Findings Using a Naïve Pooled-Data Approach - Sebbag, Lionel; Mochel, Jonathan P. (Frontiers in Veterinary Science, 2020)
This pilot study aimed to determine the plasma pharmacokinetics of prednisone and its active metabolite prednisolone following oral prednisone administration in dogs – using dosing regimens that cover anti-inflammatory to immuno-suppressive biological effects. Six healthy Beagle dogs were given 0.5, 1, 2 and 4 mg/kg prednisone orally once daily for 5 days, each successive course separated by a washout period of 9 days. At steady-state (Day 4), a sparse sampling design allowed for collection of blood from 2/6 individuals for each of the following time points: 0, 15, 30, 60, 90, 120, 240, 480 and 720 min. Prednisone and prednisolone were quantified by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Oral prednisone was rapidly converted to prednisolone in dogs (≤ 30 min), with plasma prednisolone reaching approximately 6-fold greater levels (0-656.1 ng/mL) than prednisone (0-98.8 ng/mL) overall. The ratio of plasma prednisolone/prednisone was constant across the dosing regimens, indicating a non-saturation of the hepatic 11-β-hydroxysteroid dehydrogenase that converts the prodrug to the active metabolite in dogs. The level of both corticosteroids increased with increasing dosing regimens, albeit in a non-linear manner. Non-compartmental pharmacokinetic parameters are described, including peak concentration (Cmax), time of peak concentration (Tmax), area under the concentration-time curve (AUClast) and the elimination half-life (t 1/2) for both corticosteroids, as well as clearance and volume of distribution during the terminal phase (Vz) for the administered drug (prednisone). In sum, the present study utilizes a sparse sampling and naïve pooled-data approach to estimate pharmacokinetic parameters for prednisone and prednisolone, providing supporting preliminary knowledge that can be used to optimize corticosteroid efficacy and minimize toxicity in canine patients.